Embryonic stem cells for lung fibrosis Is it the Prometheus myth or the Pandora’s Box? - Tzouvelekis, Argyris; Bouros, Demosthenes (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Three thousand years ago the Greek epic narrative poet Hesiod introduced to humanity his earliest work called “Theogony” where he narrates the myth of “Prometheus” who provoked Zeus’ wrath by stealing fire from the Gods and delivering it to humans. ...